RETRACTED: Modern design solutions in the design of boiler units, ovens and fireboxes burning solid fuel in a fluidified bed - Feoktistov I.I.; Kovalev D.S.; Shaikh M.; Chechetkin D.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001